Synthesis Of Novel Carbon Dots From Polyalthia Longifolia Leaf For In Vitro Cytotoxicity Against Hela Cells - Shuraish, Paveethra (2024)
Carbon dots (CDs), known for their outstanding fluorescence properties, have found extensive applications in medicine and pharmacy owing to their biocompatibility and nano-sized attributes. However, the potential cytotoxic effects of CDs derived from Polyalthia longifolia rich with various pharmacological activity remain underexplored. To address this gap, the current study synthesized, characterized, and investigated the toxicity against RAW264.7 cells, as well as photoinduced cytotoxicity against HeLa cells of the CDs derived from P. longifolia. Various methods, including transmission electron microscopy (TEM), X-ray diffraction (XRD), ultraviolet-visible (UV-vis) spectroscopy, zeta potential, and Fouriertransform infrared spectroscopy (FTIR), were employed to characterize the CDs. Additionally, the toxicity of the synthesized CDs was evaluated against RAW 264.7 cells, and the photo-induced cytotoxicity was assessed against HeLa cells under white light. Moreover, the impact of photo activation on ROS generation in HeLa cells also investigated. The synthesized spherical black spheres exhibited an average size of 6.29 ± 0.31 nm (TEM), consisting of both crystalline and amorphous phases of carbon (XRD), and a negative zeta potential of -20.7 ± 2.01 mV. The synthesized CDs emitted blue fluorescence when exposed to UV light at 365 nm and exhibited a prominent UVvisible absorption peak in the UV region. FTIR analysis revealed the existence of diverse functional groups on the CDs. The toxicity evaluation of synthesized CDs indicated low toxicity, promoting RAW264.7 cell viability within the 500–8000 μg range (P<0.05).